The Implementation of Story Completion Technique to Improve Speaking Skill of Vocational High School Students - Pungky Purwasih (English Education Department Slamet Riyadi University Surakarta, 2019)
The aims of this research are to find out whether Story Completion technique can improve speaking skill and to find out how Story Completion technique can improve speaking skill of the tenth grade students of SMK WIJAYA KUSUMA Surakarta in the academic year of 2017/ 2018. This research was conducted at the tenth grade students of SMK WIJAYA KUSUMA Surakarta in the Academic Year of 2017/2018. The researcher used Classroom Action Research which was conducted from January until February 2018 at the class of X.B. The research was conducted in two cycles and each cycle consisted of two meetings and one test. Each cycle also consisted of identifying the problem, planning the action, implementing the action, observing, reflecting and revising the plan. The researcher used qualitative and quantitative data to collect the data. In collecting the qualitative data, the researcher used interview, observation, and documentation. While in collecting the quantitative data, the researcher used pre-test, post-test 1 and post-test 2. To analyze the data, the researcher used qualitative and quantitative method. The result of the study showed that the mean score of students from pre-test until post-test 2 increased. The mean score of pre-test was 52.84, the mean score of post-test 1 was 64.21, and the mean score of post-test 2 was 73.68. There were also significant improvement of the students’ motivation, confident and situation in teaching and learning process. The class was more conducive. The students was interested with the activity. They enjoyed the teaching and learning process. It made the students could speak English well and confidently. It can be concluded that Story Completion Technique can improve students’ speaking skill in teaching and learning process. Keywords: Speaking Skill, Story Completion Technique, Classroom Action Research, qualitative and quantitative